PEMBERIAN JUS TOMAT UNTUK MENINGKATKAN KADAR HEMOGLOBIN IBU HAMIL DENGAN ANEMIA RINGAN - Khairati Pardila, Ulfa; Lestari Nurul Aulia, Devy (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
Anemia remains a prevalent health issue today, characterized by a low level of blood hemoglobin, and is the most prevalent type of malnutrition globally. The presence of anemia on the Global Burden of Disease 2004 list, which includes 1.159 billion people globally (approximately 25% of the world's population), demonstrates this. Approximately half of anemia cases are due to a lack of iron. Anemia can be treated non-pharmacologically with tomato juice instead of relying solely on iron tablets. The goal of this ongoing care is to investigate the impact of providing tomato juice to expectant mothers with slight anemia at HJ Hospital. In 2024, Halimah will be in Batam City. The research method used in this Continuity of Care is descriptive research incorporating a case study approach. Tomato juice is administered daily for a week. The easy touch GC Hb is the tool utilized to measure hemoglobin levels both pre and post tomato juice consumption. The study discovered that after consuming tomato juice daily, the mother's hemoglobin level rose by 1.1 g/dl From 9.9 grams per deciliter to 10.9 grams per deciliter. The overall finding suggests that administering tomato juice to expectant mothers with slight anemia has an impact. Pregnant women are advised to drink tomato juice regularly and ensure they rest enough to avoid anemia